162k views
3 votes
Which of the following is the result of using the remainder theorem to find F(-2)

for the polynomial function F(x) = -2x3 + x2 + 4x-3?
A. 9
B. -11
C.3
D. -23

User Joanna
by
6.7k points

2 Answers

2 votes

Answer:

A

Explanation:

Evaluating F(- 2) gives the remainder on dividing the polynomial by (x + 2)

F(- 2) = - 2(- 2)³ + (- 2)² + 4(- 2) - 3 = 16 + 4 - 8 - 3 = 9 ← remainder

User Saurabh Nanda
by
5.6k points
5 votes

Answer:

A. 9

Explanation:

F(-2) = 9

We are given the polynomial function;

F(x) = -2x3 + x2 + 4x-3

In order to determine F(-2) using the remainder theorem, we plug in -2 in place of x in the equation and simplify;

F(-2) = -2(-2)^3 + (-2)^2 + 4(-2) - 3

F(-2) = 9

User Zswang
by
5.6k points